TINGGALAN AREKOLOGI DI PURA DANGKA TAMBAWU DENPASAR: KAJIAN BENTUK, FUNGSI, DAN LATAR BELAKANG KEAGAMAAN - Basudewa, Dewa Gede Yadhu (Humanis, 2016)
Archaeology is the discipline knowledge that studies and reconstruct the past history of human culture through objects left behind. Bali archaeological relics are still preserved and used, one of which is the archaeological relics at the Dangka Tambawu temple in Denpasar. The problems to be discussed in this research is to know the form, function, and religious background in the archaeological relics of the Dangka temple in Tambawu . The method that used to solve the problems in this study are, first stage is collecting data by observation, interviews, and literature. The second stage is processing the data by analyzing the data using qualitative analysis, iconography, and ikonometri The theory used in this study are functional and religion theory.                The results of the analysis can show the shapes of archaeological relics at the Dangka Tambawu temple in Denpasar are form of figures of gods, rides, as well as fragments of statues and buildings. Statuettes are  not in accordance with the provisions of the Indian iconometric . The function of the archaeological relics have been sustain the function of continuity, that is as a media to ask the salvation, self-cleaning, fertility for the community and pets society. The religious background that expanded in the past is Hinduism with some sects, such as Shiva Sidhanta, Pasupata, Ganesha, and Wesnawa. And now the sects is no longer known, the society or penyungsung the temple just believe in the Almighty God (Sang Hyang Widhi Wasa ) and their sacred ancestral spirits.
Keywords: archaeological relics, form, function, religious background